Ascertainment of intimate partner violence using two abuse measurement frameworks. Issue 2 (3rd April 2006) - Bonomi, A E; Thompson, R S; Anderson, M; Rivara, F P; Holt, V L; Carrell, D; Martin, D P
Abstract : Objective: To estimate prevalence of intimate partner violence (IPV) according to two abuse ascertainment tools, and agreement between the tools. Methods: 2504 women randomly selected from a health maintenance organization were asked about IPV exposure in their most recent intimate relationship using five questions on physical and sexual abuse, and fear due to partner's threats and controlling behavior from the Behavioral Risk Factor Surveillance Survey (BRFSS) and 10 questions from the Women's Experience with Battering (WEB) scale. IPV prevalence was estimated according to the BRFSS and WEB, and the proportion of women who were WEB+/BRFSS+, WEB−/BRFSS−, WEB−/BRFSS+, and WEB+/BRFSS−. Results: In their most recent relationship, 14.7% of women reported abuse of any type on the BRFSS versus 7.0% on the WEB scale. In direct comparisons of the WEB and BRFSS questions, a higher percentage of abused women reported any IPV on the five BRFSS questions (88.4%) compared to the 10 WEB questions (42.0%). However, both the BRFSS and WEB identified some women as abused that would have been missed by the other instrument. Conclusions: Intimate partner violence prevalence depends on how women are asked about abuse. Resources permitting, more than one abuse ascertainment strategy (for example, both the BRFSS and WEB questions) should be tried in order to broadly identify as many women as possible who interpret themselves as abused.